Electrochemical behavior of non‐functionalized and sulfonated melanins at different pH values - Guerra, Nayrim Brizuela [UNESP]; Lima, João Victor Morais [UNESP]; Paulin, João Vitor [UNESP]; Nozella, Natan Luiz [UNESP]; Boratto, Miguel Henrique [UNESP]; Nogueira, Gabriel Leonardo [UNESP]; Bufon, Carlos César Bof [UNESP]; de Oliveira Graeff, Carlos Frederico [UNESP] (Wiley, 2024)
Abstract Melanins are macromolecular pigments widely spread in many living organisms, with unique physical and chemical properties. Specifically, their conductive properties have drawn attention for applications in different devices; however, the electrochemical response is equally necessary for designing technologies in sustainable bioelectronics. In this sense, we report a comparative study of the redox electrochemical properties of non‐functionalized and sulfonated melanins in different pH environments. The electrochemical response was investigated using cyclic voltammetry, electrochemical impedance spectroscopy, dielectric permittivity and AC/DC conductivity at pH 3, 5 and 7. The voltammetric currents were higher at low pH, in agreement with the known proton transport properties of melanins. The effect of pH on electrochemical properties was slightly more significant in non‐functionalized pigments. Melanins with a higher 5,6‐dihydroxyindole carboxylic acid/5,6‐dihydroxyindole ratio showed high DC current and low impedance. No significant difference was observed in the dielectric relaxation process between the different samples. © 2024 Society of Chemical Industry.